Prevention of Side effects associated with COVID 19 Vaccinations: A Review - Deshmukh, Haridhnya S; Khodke, Shruti S; Raut, Payal S; Sheikh, Aijaz A.; Biyani, Kailash. R. (Asian Journal of Pharmaceutical Research and Development, 2025)
Globally, the new SARS-CoV-2, which is responsible for COVID-19, represents a considerable burden on both health and the economy. Although there have been a great number of clinical investigations, there is not yet a single therapy or medicine that has been licensed for successful treatment. Over 300 million people have lost their lives as a result of the COVID-19 epidemic, and there is an increasing demand for anti-viral medication. Following the COVID-19 pandemic, extensive international research has led to the development of effective vaccines. However, due to the crisis, some potential side effects have been overlooked. Common complications include cerebrovascular disorders, transient ischemic attacks, intracerebral hemorrhage, ischemic stroke, and demyelinating disorders. These effects are often acute and transient but can be severe and even fatal in a few cases. This review examines the immunological and autoimmune adverse events associated with COVID-19 vaccines, highlighting their frequencies, reported cases, and associations with specific vaccine classes. The concept of vaccine-induced immune thrombotic thrombocytopenia is crucial in addressing vaccine skepticism. Healthcare professionals and public health agencies must actively monitor and address these adverse events promptly disclose suspicious incidents, take measures to mitigate dangers, and inform the public with transparency and accurate information. Continuing research and surveillance are essential for understanding the underlying mechanisms of these adverse events and developing strategies to minimize their occurrence.